Profil Emergent Critical Thinker Mahasiswa Calon Guru Matematika dalam Menyelesaikan Permasalahan Pola Linear - Diesty Hayuhantika (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2019)
Critical thinking is an important ability that must be owned by preservice teachers of mathematics, for self competence, provision of pedagogical ability, as well as in mathematicl context. The moment of the emergence of critical thinking ability need to be a special attention by educators in order to be able to design learning which facilitate the development of that critical thinking ability. This article aimed to describe critical thinking profiles of undergraduate preservice teacher mathematics in solving linear pattern problem at level emergent critical thinker. The case study is performed to two undergraduate students of mathematics department at STKIP PGRI Tulungagung who reflect that level in solving linear pattern problem in the paving tiling context. The result of the case study showed that the critical thinking ability of preservice teachers begin emerge on interpretation, analysis, inference, and explanation aspects but still lack on evaluation and self-regulation aspects.